TRANSFORMASI SISTEM IRIGASI SUBAK YANG BERLANDASKAN KONSEP TRI HITA KARANA - WINDIA, WAYAN; PUSPOSUTARDJO, SUPRODJO; SUTAWAN, NYOMAN; SUDIRA, PUTU; SUPADMO ARIF, SIGIT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005, 2012)
Subak irrigation system beside as an appropriate technological system, but as a cultural system as well. This fenomenon indicate that basically subak irrigation system is a technological system that has been developed as a part of cultural society. Because subak system is viewed as a technological system, so this system has an ability to be transformed. Meanwhile, limitation of the ability of subak irrigation system to overcome the extreem conditions, basically can be solved through the harmony and togetherness, based on the Tri Hita Karana (THK) principles as a basic of subak system. Futhermore, through inverse technique, it can be seen the ability of subak system, that can be transformed. And then, through Fuzzy Set Theory, it can be seen the dominance or ranks of the all elements of subak system, which are also as a consideration on the transformation process.
Keywords: Transformation; Subak Irrigation System.